Antioxidant Testing and Identification of Bioactive Compounds in Ethanol Extract of Propolis from Various Locations in Indonesia using LCMS-QTOF - Mulyati, Ade Heri; Alawiyah, Hanis; Marom, Muhamad Fathul; Warnasih, Siti (Departemen Kimia, 2024)
Propolis produced by Trigona sp. stingless bees contains various bioactive substances including alkaloids, flavonoids, polyphenols, saponins, steroids, and terpenoids. The geographical origin of propolis production can influence its composition of secondary metabolites. This study aimed to qualitatively analyze ethanol extracts of propolis from Bintan, Lampung, and Makassar, and evaluate their phenolic and flavonoid contents, as well as antioxidant activities. The extraction method employed kinetic maceration with continuous stirring over 24 hours, using 70% ethanol as the solvent. Additionally, antioxidant activity was assessed using the DPPH method. The qualitative phytochemical analysis revealed that all three ethanol extracts contained alkaloids, flavonoids, and polyphenols. Saponin compounds were uniquely identified in the Makassar ethanol extract. Furthermore, antioxidant activity tests indicated significant potential in all three propolis extracts. These findings highlight the potential of Trigona sp. Stingless bee propolis as a valuable source of bioactive compounds beneficial for human health.